A variation of the Pictet-Spengler reaction via a sequential reduction-cyclization reaction of N-acylcarbamates: synthesis of 1-substituted tetrahydroisoquinoline derivatives - Chutima Kuhakarn (2018)
A new variation of the Pictet-Spengler reaction for the synthesis of 1-substituted tetrahydroisoquinoline derivatives has been developed. The reaction employs the reduction of N-acylcarbamates by DIBAL-H followed by simultaneous cyclization mediated by BF3·OEt2. The synthetic potential of this method has been illustrated by the synthesis of the tetrahydroisoquinoline alkaloids, (±)-xylopinine, (±)-laudanosine, (±)-8-oxo-O-methylbharatamine, and (±)-isoindoloisoquinolone. © 2007 Elsevier Ltd. All rights reserved.